Towards new Triple Helix organisations? A comparative study of competence centres as knowledge, consensus and innovation spaces - Meyer, Martin; Kuusisto, Jari; Grant, Kevin; De Silva, Muthu; Flowers, Stephen; Choksy, Umair (Wiley, 2019)
This contribution explores new organisational forms facilitating Triple Helix relations. Analysts have pointed to the blurring of institutional boundaries and the emergence of hybrid organisations at the interface between university, industry and government. Starting out from the notion that Triple Helix organisations develop and maintain knowledge, consensus and innovation spaces, we explore four cases of competence centres that operate in this context. Comparing them, we identify Finnish SHOK centres as the most radical departure from more traditional forms of university–industry collaboration. These can be characterised as independent legal entities that are involved in integrating a large, possibly cluster‐level or technology‐focused network, defining the agenda for specific specialisation areas by engaging in all or most of the Triple Helix spaces. We argue they could be better positioned than existing intermediary organisations to deliver the Triple Helix concept.